Design and Development E-Learning Application for GMAT Course - Alblehai, Fahad Mohammed (2010)
Over the last years, e-learning has addressed a useful knowledge representation by describing learning materials based client or user behaviors. E-training is a multi-dimensional activity where each dimension should be most organization adequately supported by an E-training system to provide fruitful training materials to those are interest to read by online, a new experience for most users. Many problems faced the students during attending the classes, which disable class improvement for understanding learning materials. Therefore this study focus on development of an e-learning system as a learn material for GMAT course, the proposed learning system has been designed using PHP language and MYSQL. Additionally, this study provided interactive e-learning system for learning GMAT course by saving the student time to attend the classes.